Magnitude and Determinant Factors of Postpartum Depression Among Mothers Attending Their Postnatal and Vaccination Services at Public Health Institutions of Addis Ababa, Ethiopia - Wake, Getu Engida; Fitie, Girma Wogie; Ashenafi, Betelhem; Tadese, Mesfin; Tessema, Saba Desta (Frontiers in Public Health, 2022)
Background The postpartum period is known as a high-risk period for the onset of different maternal mental health problems. Globally, 10–20% of postnatal mothers suffer from depressive symptoms. This study aimed to assess the magnitude and determinant factors of postpartum depression among mothers attending their postnatal and vaccination services at public health institutions in Addis Ababa, Ethiopia. Methodology Health institution-based cross-sectional study was conducted among 461 postnatal mothers attending public health institutions in Addis Ababa from 15 May 2021 to 15 July 2021. A multistage sampling technique was employed to select the public health institutions and a systematic random sampling method was used to get selected, postnatal mothers. Epidata version 3.1 and SPSS version 25 were used for data entry and analysis, respectively. P-value ≤ 0.05 was used as a cut point of statistical significance in multivariable binary logistic regression. Results From total postnatal mothers 91(19.7%) of them had postpartum depression. Occupational status [AOR = 3.39, 95% CI: 1.04, 8.15], marital status [AOR = 2.69, 95% CI =1.33, 5.45], income management [AOR = 3.76, 95% CI: 1.53, 8.21], sex of baby [AOR = 5.07, 95% CI: 1.24, 20.69], history of child death [AOR = 6.93, 95% CI: 2.67, 15.79], unplanned pregnancy [AOR = 3.08, 95% CI: 1.65, 7.93], negative life event [AOR = 2.39, 95% CI: 1.03, 5.39], substance use during pregnancy [AOR = 6.23, 95% CI: 2.72, 20.05], history of depression [AOR = 5.08, 95% CI: 1.79, 14.39], and marriage satisfaction [AOR = 6.37, 95% CI: 2.63, 14.29] were determinant factors of postpartum depression. Conclusion The prevalence of postpartum depression in this study is high compared to national findings. Occupational status, marital status, income management, sex of baby, history of child death, unplanned pregnancy, negative life event, substance use during pregnancy, history of depression, and marital satisfaction were determinant factors of postpartum depression. The ministry of health should integrate mental health services with existing maternal health care services. It would be better if all healthcare professionals working in the maternal and child health unit will routinely screen postpartum depressive symptoms and link them to mental health services.